FORESTRY PARTNERSHIP SCHEME IN SOCIAL FORESTRY PROGRAM ON FOREST FARMERS GROUPS IN FOREST AREAS WITH THE SPECIAL PURPOSE OF SISIMENI SANAM, FATULEU SUBDISTRICT, KUPANG REGENCY - Emanuella Elma Intania Logo; Lusia Sulo Marimpan; Nixon Rammang; Roni Haposan Sipayung (Journal of Scientech Research and Development, 2024)
Forestry Partnership scheme in Social Forestry Program is one of the programs implemented by the government to overcome the problem of forest destruction and deforestation. This research aims to determine the effectiveness of the Social Forestry Program and Forestry Partnership Scheme in preserving forest areas and improving the welfare of communities around forest areas. The research uses observation methods to determine plant types, interviews, and Good Services Ratio (GSR) analysis for the socio-economic characteristics of the community and the rate of land cover change using spatial analysis (Geographic Information System). The results of the research show that the Social Forestry Program Forestry Partnership Scheme is less effective in terms of conserving forest areas; this is indicated by changes in land cover conditions in 2013, 2018, and 2023, that forest land decreased by 19%, mixed plantations increased by 11.42 %, and settlements increased by 7.58%. The planting pattern used by members of the forest farmer group is agroforestry, which combines forestry crops with annual crops. The Forest Farmer Group in the Forestry Partnership program is running effectively economically, with a total economic value of 64,231,000 IDR per year, with the highest utilization being Cashew nuts at 71%. Respondents' income was very effective by 85%. The social aspect is less practical regarding respondents' welfare, with an average value of 2.59, meaning they are classified as less prosperous.